Analysis of the Heat Capacity for Pure CH4 and CH4/CCl4 on Graphite Near the Melting Point and Calculation of the T–X Phase Diagram for (CH3)CCl3+CCl4 - Yurtseven, Hamit; Yilmaz, Aygül (Frontiers in Physics, 2016)
We study the temperature dependence of the heat capacity Cp for the pure CH4 and the coadsorbed CH4/CCl4 on graphite near the melting point. The heat capacity peaks are analyzed using the experimental data from the literature by means of the power-law formula. The critical exponents for the heat capacity are deduced below and above the melting point for CH4 (Tm = 104.8 K) and CH4/CCl4 (Tm = 99.2 K). Our exponent values are larger as compared with the predicted values of some theoretical models exhibiting second order transition. Our analyses indicate that the pure methane shows a nearly second order (weak discontinuity in the heat capacity peak), whereas the transition in coadsorbed CH4/CCl4 is of first order (apparent discontinuity in Cp). We also study the T – X phase diagram of a two-component system of CH3CCl3+CCl4 using the Landau phenomenological model. Phase lines of the R+L (rhombohedral+liquid) and FCC+L (face-centred cubic + liquid) are calculated using the observed T – X phase diagram of this binary mixture. Our results show that the Landau mean field theory describes the observed behavior of CH3CCl3+CCl4 adequately. From the calculated T – X phase diagram, critical behavior of some thermodynamic quantities can be predicted at various temperatures and concentrations (CCl4) for a binary mixture of CH3CCl3+CCl4.